Let's get better vets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
An October 2002 seminar on Primary Animal Health Care in the 21st Century in Mombasa, Kenya, focussed the minds of 120 specialists from 20 African states, South- and South-East Asia, South America and Europe. In debating how to shape the rules,...